Landasan Psikologis dalam Kurikulum Bimbingan Konseling - Nuzliah Nuzliah (Indo Publishing, 2025)
The guidance and counseling curriculum is a crucial component of the education system, aiming to support optimal student development. In its design, the guidance and counseling curriculum must be grounded in psychological foundations as a reference for understanding the needs, characteristics, and dynamics of individual development. This article discusses in depth the contributions of psychological theories, such as developmental psychology, educational psychology, and personality psychology, in developing a relevant and effective guidance and counseling curriculum. The research method used in this study is library research, with journals as primary sources.